Thirdyear medical students’ and clinical teachers’ perceptions of formative assessment feedback in the simulated clinical setting - Reina Abraham; Veena Singaram (South African Medical Association, 2016)
Background. Clinical skills training in the clinical skills laboratory (CSL) environment forms an important part of the undergraduate medical curriculum. These skills are better demonstrated than described. A lack of direct observation and feedback given to medical students performing these skills has been reported. Without feedback, errors are uncorrected, good performance is not reinforced and clinical competence is minimally achieved. Objectives. To explore the perceptions of 3rd-year medical students and their clinical teachers about formative clinical assessment feedback in the CSL setting. Methods. Questionnaires with open- and closed-ended questions were administered to 3rd-year medical students and their clinical skills teachers. Quantitative data were statistically analysed while qualitative data were thematically analysed. Results. Five clinical teachers and 183 medical students participated. Average scores for the items varied between 1.87 and 5.00 (1: negative to 5:positive). The majority of students reported that feedback informed them of their competence level and learning needs, and motivated them to improve their skills and participation in patient-centred learning activities. Teachers believed that they provided sufficient and balanced feedback. Some students were concerned about the lack of standardised and structured assessment criteria and variation in teacher feedback. No statistical difference (p<0.05) was found between the mean item ratings based on demographic and academic background. Conclusion. Most teachers and students were satisfied with the feedback given and received, respectively. Structured and balanced criterion-referenced feedback processes, together with feedback training workshops for staff and students, are recommended to enhance feedback practice quality in the CSL. Limited clinical staff in the CSL was noted as a concern.